Origin of the Tongbai-Dabie-Sulu Neoproterozoic low-δ18O igneous province, east-central China - Fu, B.; Kita, N.; Wilde, Simon; Liu, X.; Cliff, J.; Greig, A. (Springer, 2013)
Zircons from 71 diverse rocks from the Qinling-Tongbai-Dabie-Sulu orogenic belt in east-central China and, for comparison, eight from adjoining areas in the South China and North China blocks, have been analyzed for in situ 18O/16O ratio and/or U–Pb age to further constrain the spatial distribution and genesis of Neoproterozoic low-δ 18O magmas, that is, δ 18O(zircon) ≤4 ‰ VSMOW. In many metaigneous rock samples from Tongbai-Dabie-Sulu, including high-pressure and ultrahigh-pressure eclogites and associated granitic orthogneisses, average δ 18O values for Neoproterozoic “igneous” zircon cores (i.e., 800–600 Ma) vary from −0.9 to 6.9 ‰, and from −9.9 to 6.8 ‰ for Triassic metamorphic rims (i.e., 245–200 Ma). The former extend to values lower than zircons in primitive magmas from the Earth’s mantle (ca. 5–6 ‰). The average Δ 18O (metamorphic zircon − “igneous” zircon) values vary from −11.6 to 0.9 ‰.The large volume of Neoproterozoic low-δ 18O igneous protoliths at Tongbai-Dabie-Sulu is matched only by the felsic volcanic rocks of the Snake River Plain hotspot track, which terminates at the Yellowstone Plateau. Hence, the low-δ 18O values at Tongbai-Dabie-Sulu are proposed to result from shallow subcaldera processes by comparison with Yellowstone, where repeated caldera-forming magmatism and hydrothermal alteration created similar low-δ 18O magmas. However, the possibility of involvement of meltwaters from local continental glaciations, rather than global Neoproterozoic glaciations, cannot be precluded. Our data indicate that Neoproterozoic low-δ 18O magmas that are either subduction- or rift-related are present locally along the western margin of the South China Block (e.g., Baoxing Complex). It appears that Neoproterozoic 18O-depletion events in the South China Block as the result of hydrothermal alteration and magmatism affected a much larger area than was previously recognized.